1996
DOI: 10.1182/blood.v88.6.2004.bloodjournal8862004
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic effects of flt3 ligand in vivo in mice

Abstract: We have investigated the effects of in vivo treatment with flt3 ligand (FL) on murine hematopoiesis, including mobilization of progenitors into the peripheral blood (PB). Mice were injected once daily with 10 micrograms recombinant human FL for 15 days. On days 3, 5, 8, 10, 15, and 22, mice were killed and analyzed for the number of leukocytes and colony-forming units (CFU) in bone marrow (BM), spleen, and PB. Splenic and PB cellularity increased with time in FL-treated mice. In the spleen, there was an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(77 citation statements)
references
References 26 publications
5
72
0
Order By: Relevance
“…Studies in the mouse (Brasel et al 1996) have shown that daily administration of FL at 10 lg ⁄ mouse for 15 days by i.p. injection promotes lymphopoiesis with peripheral blood and spleen WBC counts increasing significantly.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies in the mouse (Brasel et al 1996) have shown that daily administration of FL at 10 lg ⁄ mouse for 15 days by i.p. injection promotes lymphopoiesis with peripheral blood and spleen WBC counts increasing significantly.…”
Section: Discussionmentioning
confidence: 87%
“…injection promotes lymphopoiesis with peripheral blood and spleen WBC counts increasing significantly. The experiments of Brasel et al (1996) also showed that the administration of FL had a positive effect on the number of HSCs. Indeed, HSCs characterized as lin -, Sca-1 + and c-Kit + , were found in higher numbers in the bone marrow, spleen and peripheral blood of FL-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…once daily for 10 consecutive days, a process known to expand all DC subsets without activation. 23 All DC subsets investigated in this report are present in mice that have not been treated with Flt3-L (Table 1). A single-cell suspension was prepared from the spleen, mesenteric lymph nodes (MLN), Peyer's patches (PP) and peripheral lymph nodes (PLN) (inguinal, popliteal, axillary, brachial and cervical) of treated mice by mechanical disruption of tissue (n 10 mice/group).…”
Section: Generation and Isolation Of DCmentioning
confidence: 82%
“…Chinese hamster ovary (CHO)-derived human Flt3-ligand (Flt3L) was produced and puri®ed as described previously. 23 Puri®ed and biotin-labelled anti-IL-4, anti-IL-10 and anti-IFN-g antibodies were purchased from BD Pharmingen.…”
Section: Reagentsmentioning
confidence: 99%
“…The receptor for this ligand (Flt3) is expressed in hematopoietic progenitor cells and is crucial for development of dendritic cells and enhances production of lymphoid progenitors. [35][36][37] Flt3L has been implicated as a pro-inflammatory factor in the pathogenesis of a variety of inflammatory diseases. [38][39][40] It also has been shown to have a protective, anti-inflammatory role in some animal models.…”
Section: Discussionmentioning
confidence: 99%